Ophthalmic viscosurgical device backflow into cartridge during intraocular lens insertion using injectors - Matsuura K (Dove Medical Press, 2014)
Kazuki Matsuura,1 Yoshitsugu Inoue2 1Nojima Hospital, 2Tottori University, Kurayoshi City, Tottori, Japan Background: The purpose of this study was to assess the risk of intraocular contamination caused by intraocular lens (IOL) insertion with injectors by observing the dynamics of an ophthalmic viscosurgical device (OVD). Methods: Each type of injector was equipped with a colored OVD and IOL, and a 2 mm length from the tip of the cartridge was replaced with a colored OVD. The various combinations of IOLs and injectors used were: a three-piece shaped IOL, VA60BBR + TypeE1 (HOYA incision size 2.5 mm; group A, n=5); a single-piece IOL, 251+ iSert micro, preloaded (HOYA, incision size 2.2 mm; group G, n=5); and a single-piece IOL, SN6CWS preloaded (Alcon, incision size 2.7 mm; group C, n=5). Results: In group A, the intraocular OVD instantly flowed backward into the injector, whereas the colored OVD was pushed backward deep inside the cartridge without flowing into the eye. In group B, the backflow of the intraocular OVD into the injector was limited, resulting in the influx of a large amount of the colored OVD into the eye along with the IOL. In group C, as in group A, a large amount of the intraocular OVD flowed backward into the injector. Consequently, a small amount of the colored OVD flowed into the eye. Conclusion: The tip of the injector and OVD could be contaminated because the surgical field cannot be completely sterile, even after preoperative disinfection. Our experiments revealed that OVD backflow into the injector cavity occurs during IOL insertion, and this phenomenon may have minimized intraocular contamination. However, small-diameter cartridges along with plate-type haptics allow insufficient OVD backflow, resulting in intraocular influx of the contaminated OVD. Surgeons have to be notified that intraoperative bacterial contamination can occur even after IOL insertion using injectors. Keywords: intraocular lens insertion, endophthalmitis, injector, backflow, ophthalmic viscosurgical device